Effect of Capsule Density and Concentration on Pressure Drops of Spherical Capsule Train Conveyed by Water - Ulusarslan, Deniz (ASME-AMER SOC MECHANICAL ENG, 2010)
This experimental investigation concerns the hydraulic transport of a spherical capsule train, whose density is equal to that of water (relative density; s=1), in horizontal pipes. In a system where the carrier fluid is water, pressure drops of two phase flow and capsule velocities were measured at 0.2-1.0 m/s bulk velocities and 5-20% capsule transport concentrations. The results found were compared with the pressure gradient (pressure drops per unit length) ratios ((Delta P/L)(m)/(Delta P/L)(w)) measured for less dense capsules. The capsule velocity and the velocity ratio (V(c)/V(b)) increased with increasing the bulk velocity. As concentration increases, the pressure gradient of the capsule-water mixture increases. For all concentrations, the pressure gradient ratio decreases (getting closer to 1) with increasing bulk velocity. This result is similar to that of capsules with less relative density. However, the pressure gradient ratio of the capsule flow with less density is higher than that of capsules with equal density at constant transport concentrations. The reason for this difference is that the capsules with a density equal to that of water move along the axis of the pipe for a longer time. When capsules with equal density are used, the mass flow rate will remain the same, but energy consumption will decrease.
Keywords: pipe flow; two-phase flow; PIPELINE FLOW; SINGLE CYLINDRICAL; TRANSPORT; VELOCITY; LIQUID; OIL; Engineering